Human Sciences in the Third Generation of University Phenomenological Analysis of the Barriers of the Entrepreneur Human Sciences - Fatemeh Khoshnevisan; Abbas Abbaspour; Nematollah Fazeli; Mohammad Reza Neyestani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study was conducted with the aim of a phenomenological investigation of the barriers to entrepreneurship in the Human Sciences at university. The research method was qualitative with a phenomenological approach. The study population included experts in the field of human sciences and humanities. The purposeful research sampling method was done, which was saturated theoretically with 12 people. The data collection tool was a semi-structured interview. The research reliability of the data was confirmed by the criteria of Lincoln and Guba (1985) and also the method of Denzin (1978) and Patton (1999). The data analysis was an inductive method using a seven-step put forth by Colaizzi (1978). The results showed that in the dimension of employment, two distinct, opposite, and consistent views of the business of the humanities were appreciable. In the category of social acceptance, reduced social status, applied reductions, cultural, spatial planning, discretion in the discourse of the humanities, unknowing social knowledge, and knowledge in the university. In the category of the developmental infrastructure of these sciences, we can refer to objective growth, gender reversal, functional capability, digitization, conflicts of power. In the category of humanities development, lack of the issue, the ability of humanities research, the entrepreneurship of the humanities, the possibilities for the internationalization of these sciences, and the emergence of interdisciplinary science can be enumerated.